Weihnachtsausstellung 1997-1998 mit 33 Berner Künstlerinnen. - Kunsthalle Bern, Bern; Fibicher, Bernhard (Bern : Kunsthalle Bern, 1997)
Abbühl-Picon, Adela ; Baumann, Marianne ; Betulius, Syl ; Brändli, Susanne ; Bünter, Renata ; Feldmann, Evelyne ; Freidig, Marianne ; Freudiger, Christine ; Grau, Pascale ; Wyrsch, Gertrud Guyer ; Haudenschild, Katharina ; Hostettler, Sylvia ; Kulicka, Sabina ; Künzler, Heidi ; Leistner, Verena ; Leuenberger, Karin ; Loux, Andrea ; Maibach, Ida ; Meyer-Cesta, Barbara ; Michel, Chantal ; Moser, Ka ; Nydegger, Anita ; Sauter, Dorothee ; Schär, Susanne ; Schneiter, Yolande ; Schubiger, Irene ; Schwab, Verena ; Strub, Simone ; Vuille, Anita ; Walpen, Sibylla ; Wirz, Katrin ; Zaugg, Simone ; Zulauf, Esther
Weihnachtsausstellung 1997-1998 mit 33 Berner Künstlerinnen, Kunsthalle Bern, 12. Dezember 1997 - 8. Januar 1998
Duits
boek